Moderating effects of attributions on the relationship between emotinal dissonance and surface acting: a transactinal approach to health care professionals' emotion work - Crego, Antonio; Martinez-Inigo, David; Tschan, Franziska (My University, 2013)
Based on a transactional model of stress, this study aims to understand the role played by attributions in selecting surface acting as emotion regulation strategy whencopingwithemotion-ruledissonance.Asampleofprimaryhealthcareprofes- sionals (n = 87) based in Madrid filled in a questionnaire. Hierarchical multiple regression analyses were conducted to test hypotheses on the moderating effects of attributions on the relationship between emotion-rule dissonance and surface acting.Resultsshowedthathighlevelsof attributiontopatientsof responsibilityfor negative events, low levels of professionals’ self-accountability, and low attribution of being able to promote a positive change strengthen the positive association betweenemotion-ruledissonanceandsurfaceacting.Thiscouldexplainwhyprofes- sionalsuseapotentiallydamagingemotionregulationstrategy.